Pengaruh Model Pembelajaran Game Based Learning terhadap Motivasi Belajar Peserta Didik - Islam, Kireida Rona; Komalasari, Kokom; Masyitoh, Iim Siti; Juwita, Juwita; Adnin, Ismi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
The implementation of inappropriate learning models can disrupt the learning environment, potentially demotivating learners, affecting their academic performance and overall development. The purpose of this research is to explore the effect of implementing GBL (game-based learning) in schools on learners' interest or motivation to learn. This research uses a qualitative approach by applying literature review and comparative study as methods. The results show that game-based learning can increase students' participation, improve students' learning motivation and offer additional motivation beyond what can be obtained from traditional methods.